SPECTRUM OF CONGENITAL HEART DISEASE IN FULL TERM NEONATES - Bibi, Saima; Gilani, Syed Yasir Hussain; Bibi, Shawana (Journal of Ayub Medical College Abbottabad, 2018)
Background: Congenital heart disease is a significant problem world over especially in neonates. Early diagnosis and prompt interventions in neonatal period precludes the mortality associated with this disorder. The objective of this study was to highlight the diversity of congenital cardiac defects in our region so that appropriate interventions are devised to minimize significant morbidity and mortality associated with this disorder. Methods: This descriptive cross-sectional study was conducted at the Neonatology Unit of Department of Paediatrics, Ayub Teaching Hospital from January 2015 to December 2016. Approval of ethical committee was taken. All full-term neonates of either gender who presented in department of neonatology including those delivered in hospital or received from other sources (private settings, home deliveries), diagnosed as having congenital heart disease on echocardiography were included in the study. Preterm neonates of either gender were excluded from the study. Patient characteristics were recorded in a designed proforma. Data was entered in SPSS version 20 and analysed. Results: A total of 89 neonates were included in the study. Mean age of presentation was 6.34±7.058 days and range of 1-28 days. There was a male preponderance with 57 (64%) male patients as compared to 32 (36%) female patients. Ventricular septal defect (VSD) was the commonest cardiac lesion being present in 34 (38.2%) patients. Other defects included complex congenital heart disease in 8 (9%), atrial septal defect (ASD) and transposition of great arteries (TGA) in 7 (7.9%) each, atrioventricular septal defect (AVSD) in 6 (6.7%) and Fallots’s tetralogy (TOF) and hypoplastic left heart syndrome in 5 (5.6%) each. Conclusion: Congenital heart disease is a problem of profound importance. It constitutes approximately one third of the total major congenital malformations. There is a diversity of cardiac lesions in our region that warrant early and prompt interventions so that the disease is recognized and treated at the earliest to reduce morbidity and mortality. Keywords: Congenital heart disease; ventricular septal defect; cyanotic